Identification of some kefir microorganisms and optimization of their production in sugarcane juice (2016)
Kefir grains are a consortium of bacteria and yeasts grouped in a polysaccharide called kefirano. They ferment sugar substrates to produce organic acids, CO2, vitamins and ethanol. They also have positive effects on health. This research project aimed to optimize the fermentation process of sugarcane concentrate using kefir grains. The microorganisms were first identified morphologically and biochemically, then isolated and purified in selective media. Optimization was conducted using the response surface methodology with a composite central design. The independent variables were: temperature, time and percentage of kefir grains added. As for dependent variables, we considered the following: increase in kefir grains (also measured as a percentage), acidity and microbial growth. Additionally, our study identified populations of Lactobacillus curvatus and the following yeasts: Candida famata, Can. magnoliae, Can. krusei/incospicua and Can. sphaerica in the kefir grains. The optimal conditions were 33.5 °C, 30 h and 6% w/w of added kefir grains. The increase in kefir grains reached was of 193 ± 12%. The lactobacilli, lactococci and yeast counts were 1.57x108, 8.63x107 and 2.05x107 CFU mL-1 respectively. Experimental optimization was an effective tool for the fermentation of kefir grains in sugarcane concentrate.